Investigating the Impact of the First and Second Waves of the COVID - 19 Pandemic on the Indian Stock and Commodity Markets : An ARDL Analysis of Gold, Oil, and Stock Market Prices - Syed, Aamir Aijaz; Tripathi, Ravindra; Deewan, Jyoti (Indian Journal of Finance, 2021)
COVID - 19 and its consequential impact on the economic fundamentals are highly discussed topics among the researchers. However, there is a literature void in the context of the Indian commodity and financial markets. To bridge this gap, the current study tried to investigate the influence of COVID -19 on the Indian commodity and financial markets by taking the data of the National Stock Exchange of India representing financial markets and the gold prices & oil prices representing commodity markets. The data were segregated into three-time lines, that is, whole period (April 1, 2020 – April 10, 2021), first wave (June 6 – September 30, 2020), and second-wave (February 2 – April 10, 2021) and to investigate the above relationship, the autoregressive distribution lag (ARDL) approach was employed. The findings suggested that during the whole period of the study and the first wave, coronavirus spread had a significant negative influence on the oil prices and the stock market. However, the impact was significant and positive for gold prices. The Wald test also confirmed a long-run cointegration among the variables in both periods of the study. In the context of the second wave, the study contradicted the above findings and concluded that during the second wave, the spread of COVID-19 cases had a positive impact on oil prices and stock markets; whereas, there was a negative impact on the gold prices. The findings highlighted the issue of uncertainty of pandemic, symmetry, demand theory and also highlighted the inverse relationship of gold and equity instruments, which will help in making appropriate policy-oriented decisions.